JUMLAH PLATELET PADA PENDERITA PRE-EKLAMPSIA - M. Arif Muchlis; Suci Aprianti; Hj. Darmawati ER (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
In pregnant women who previously did not have hypertension pre-eclampsia is a pregnancy complication, which characterized by the increased of blood pressure, proteinuria and/or oedema. One of theory about aetiology of pre-eclampsia suggests that this is caused by endothelial damage that can lead to adhesion and platelet aggregation. The aim of this study was to know the platelet count and indices by analyzing, such as mean platelet volume (MPV), its distribution width (PDW) and the large cell ratio (P-LCR) for diagnostic confirmation in pre-eclampsia patients. This research was a retrospective study using secondary data of routine blood test from medical records of pre eclampsia patients who were treated at Dr. Wahidin Sudirohusodo Hospital during the period of January to December 2011 and the normal pregnant women data that were taken as control. The data obtained were platelet count, MPV, PDW, P-LCR and analyzed using independent T test. The results showed that the mean platelet count in pre-eclampsia patients was lower than the control but had no statistically significant difference (p=0.325) whereas the mean of MPV, PDW and P-LCR in pre-eclampsia patients increased compared to the control group and was statistically significant with p value of MPV (p=0.003), PDW (p=0.002) and P-LCR (p=0.010). In conclusion, platelet indices can be used as diagnostic confirmation markers in pre-eclampsia patients.